783. Characterization of Non-tuberculous Mycobacteria Isolates in a National Mycobacterial Laboratory in Panama: 2012–2015. (26th November 2018) - Zavala, Sofia; Rosas, Samantha; Calvo, Arlene; Sosa, Nestor; Henostroza, German; Rodriguez, Ana Belen Arauz
Abstract: Background: Nontuberculous mycobacteria (NTM) are becoming more frequently isolated in microbiology laboratories. There is no standardized diagnosis, treatment, and/or monitoring of patients with NTM disease. We described the experience of the Panama National Mycobacterial Laboratory in isolating NTM in patients suspected to have active tuberculosis in Panama. Methods: Data registries of the National TB Program Laboratory of Panama between 2012 and 2015 were reviewed. Demographic information, relevant history, sample source, and isolate identified for each specimen obtained at the time of specimen submission was extracted. Identification of mycobacterial species were made using culture and PCR. Data were exported to an Excel workbook and a descriptive analysis was performed using STATA. Results: A total of 4, 545 samples were received during this period. Of these, 288 (6.3%) were not processed. From the remaining 4, 257 samples, 705 (16.5%) were negative, 2, 783 (65.3%) were positive for M. tuberculosis, and 769 (18%) were confirmed NTM. NTM species identification was achieved in 715 (93%) using PCR. Median age was 55 years (0 – 92); 49.4% were male. The most frequent NTM isolate was M. avium complex in 172 (22.3%) samples, followed by M. fortuitum in 131 (17%). M. chelonae was isolated in 98 (12.7%) samples, M. gordonae in 50 (6.5%), M. scrofulaceum in 20 (2.6%), and M. triviale in 16 (2.0%). NTM isolation steadily rose over the study period with 490 (63.7%) of the samples being from 2015 and 465 (94.5%) of these typified by PCR. Specimens mainly originated from the Panama metropolitan area (88.2%) and were mostly sputum samples (70.8%). Conclusion: Nontuberculous mycobacteria represented an important proportion of isolates among TB suspects in Panama. The implementation of more sensitive diagnostic techniques is increasing the recovery of NTM. Further evaluation of the clinical significance of these finding is required for appropriate guideline implementation. Disclosures: G. Henostroza, Aeras: Investigator, Grant recipient.